Bend pressure drop in horizontal and vertical dilute phase pneumatic conveying systems. (14th December 2019) - Tripathi, Naveen Mani; Portnikov, Dmitry; Levy, Avi; Kalman, Haim
Graphical abstract: Highlight: Effect of bend orientation (horiz. And vert.) on total bend pressure drop is examined. A new correlation of total bend pressure drop (TBPD) is introduced for blind-T. A new correlation of total bend pressure drop (TBPD) is introduced for radius bends. Particles can be conveyed in the vertical bend at higher than their terminal velocity. Abstract: This paper presents a detailed investigation into the modeling of the total bend pressure drop (TBPD) for all three orientations: horizontal-horizontal (H-H), horizontal-vertical (H-V), and vertical-horizontal (V-H) in dilute phase flow. Different types of materials were fed with a screw feeder and conveyed through two different sets of galvanized steel pipeline. The TBPD (all orientations) is the summation of the pressure drop due to the momentum change (reacceleration), the air only flow along the bend, and a function of the pressure drop due to the particles, which contributes to the bend only. A qualitative comparison was performed for blind-T and a radius bend (R/D = 10) using a particular material property. This comparison helped in obtaining a comprehensive understanding of TBPD.